2014
DOI: 10.1007/s11595-014-1025-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption mechanism of polycarboxylate-based superplasticizer in CFBC ash-Portland cement paste

Abstract: Circulating fl uidized bed combustion (CFBC) ash exhibits the desirable pozzolanic activity which makes it a potential supplementary cementitious material to replace cement for concrete production. However, the high unburnt carbon content and porous surface structure of CFBC ash may adsorb water reducer and thereby signifi cantly reduce the effi ciency of water-reducing agents. The adsorption mechanism of polycarboxylate superplasticizer in CFBC ash-Portland cement paste was investigated by ultraviolet-visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The free lime (f-CaO) content of FBCFA has been found to increase the water requirement [101]. Song et al [108] found that the polycarboxylate superplasticizer adsorption capacity of FBCFA-OPC paste is higher than that of PCCFA-OPC paste. Moreover, the adsorption amount of polycarboxylate superplasticizer increases with the ratio of ash to cement in the paste, and the fluidity of FBCFA-Portland cement paste is lower than that of the PCC fly ash paste.…”
Section: Partial Replacement Of Cement In Concretementioning
confidence: 99%
“…The free lime (f-CaO) content of FBCFA has been found to increase the water requirement [101]. Song et al [108] found that the polycarboxylate superplasticizer adsorption capacity of FBCFA-OPC paste is higher than that of PCCFA-OPC paste. Moreover, the adsorption amount of polycarboxylate superplasticizer increases with the ratio of ash to cement in the paste, and the fluidity of FBCFA-Portland cement paste is lower than that of the PCC fly ash paste.…”
Section: Partial Replacement Of Cement In Concretementioning
confidence: 99%
“…The mechanisms of polycarboxylate water reducing agent [14][15][16][17][18][19] are mainly explained as follows:…”
Section: Schematic Representation Of the Typical Molecular Structure ...mentioning
confidence: 99%
“…Water‐soluble comb‐like polycarboxylates contain polyethylene or polypropylene oxide side chains which are attached to the backbone . They can adsorb onto solid particles by electrostatic attraction, hydrogen bonding or van der Waals interactions . Side chains are responsible for the steric hindrance effect .…”
Section: Introductionmentioning
confidence: 99%